Antimicrobial Efficacy of Five Probiotic Strains Against Helicobacter pylori - Ilaria Maria Saracino; Matteo Pavoni; Laura Saccomanno; Giulia Fiorini; Valeria Pesci; Claudio Foschi; Giulia Piccirilli; Giulia Bernardini; John Holton; Natale Figura; Tiziana Lazzarotto; Claudio Borghi; et al. (Antibiotics, 2020)
Treatment of Helicobacter pylori (H. pylori) infection is a challenge for clinicians. The large increase in drug-resistant strains makes the formulation of new therapeutic strategies fundamental. The frequent onset of side effects during antibiotic treatment (mainly due to intestinal dysbiosis) should not be underestimated as it may cause the interruption of treatment, failure of H. pylori eradication and clonal selection of resistant bacteria. Probiotic integration during antibiotic treatment can exert a dual function: a direct antagonistic effect on H. pylori and a balancing effect on dysbiosis. Therefore, it fulfills the definition of a new therapeutic strategy to successfully treat H. pylori infection. Data reported in literature give promising but discrepant results. Aim: To assess in vitro bacteriostatic and bactericidal activity of probiotic strains against H. pylori. Materials and methods: L. casei, L. paracasei, L. acidophilus, B. lactis and S. thermophilus strains were used. Agar well diffusion and time-kill curves were carried out to detect bacteriostatic and bactericidal activity, respectively. Results: All probiotic strains showed both bacteriostatic and bactericidal activity vs. H. pylori. Conclusions: Such findings prompted us to plan a protocol of treatment in which probiotics are given to infected patients in association with antibiotic therapy.